Abrasive material for air blasting and separator for fuel cell

By using carbon powder with a new Mohs hardness of 2.5 to 7.0 for air sandblasting treatment, the problems of lowering the conductivity of the fuel cell spacer and contamination of the residue of the abrasive material after sandblasting are solved, and excellent conductivity and adhesion are achieved.

CN119654214APending Publication Date: 2025-03-18NISSHINBO CHEM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380057341.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-04
Filing Date
2023-06-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

After the existing spacers for fuel cells are blasted, conductive particles are prone to fall off, resulting in worsening of contact resistance, and residues of abrasive material may contaminate other components.

Method used

Carbon powder with a hardness of 2.5 to 7.0 is used as the abrasive material for air sandblasting, and the surface of the spacer for fuel cell is roughened to ensure that there is less residue of the abrasive material on the surface.

Benefits of technology

It is possible to realize that the grinding material is difficult to retain the surface of the spacer after sandblasting, maintain excellent conductivity and adhesion to the gasket, and reduce contact resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005259834030000121
    Figure BDA0005259834030000121
Patent Text Reader

Abstract

As a result, the polishing material for air blasting, which contains a carbon powder having a new Mohs hardness of 2.5-7.0, is less likely to remain on the surface of an object to be blasted, and therefore, there is little polishing material residue on the surface of a fuel cell separator in which at least a portion of the surface is roughened with this polishing material for air blasting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an abrasive material for air blasting and a spacer for a fuel cell. Background Art

[0002] The fuel cell separator plays a role in providing conductivity to each unit cell and in ensuring passages for fuel and air (oxygen) supplied to the unit cells and also plays a role as a boundary wall separating them.

[0003] Therefore, the separator is required to have various properties such as high conductivity, high gas impermeability, chemical stability, heat resistance, and hydrophilicity.

[0004] In order to impart these characteristics to the spacer, various techniques such as roughening the surface of the spacer by sandblasting have been disclosed in the past.

[0005] For example, Patent Document 1 proposes a technique in which conductive particles such as carbon particles are attached or recessed on the surface of a fuel cell separator composed of carbon particles and a thermoplastic resin by shot peening to reduce the contact resistance of the surface. In this technique, since the conductive particles are attached or recessed on the surface resin by shot peening, the carbon particles in the separator are prevented from falling off during the blasting, and the surface becomes rich in resin, thereby reducing the contact resistance. On the other hand, the conductive particles fall off during the assembly of the fuel cell and during power generation, resulting in a problem of deterioration of the contact resistance.

[0006] In addition, Patent Document 2 proposes a technique for treating the surface of a fuel cell separator made of a thermosetting resin or artificial graphite with an alumina abrasive. In the technique of Patent Document 2, the contact resistance is reduced by adjusting the surface of the fuel cell separator to an average roughness of 1.0 to 5.0 μm, but in this case, there is also a problem that the alumina abrasive attached to the surface of the fuel cell separator and recessed therein falls off and contaminates other fuel cell components.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2005-332775

[0010] Patent Document 2: Japanese Patent Application Publication No. 2005-197222 Summary of the invention

[0011] Problems to be solved by the invention

[0012] The present invention has been made in view of such actual circumstances, and an object of the present invention is to provide an abrasive for air blasting which is unlikely to remain on the surface of a blasting object, and a spacer for a fuel cell with little abrasive residue on the surface.

[0013] Means for solving problems

[0014] The present inventors have conducted intensive studies to achieve the above-mentioned purpose, and as a result, have found that an abrasive material for air blasting comprising carbon powder having a predetermined hardness is unlikely to remain on the surface of the blasting object after blasting, and that a fuel cell separator surface roughened by the abrasive material has less abrasive material residue, good conductivity, and excellent adhesion to a gasket, thereby completing the present invention.

[0015] That is, the present invention provides:

[0016] 1. Abrasive material for air sandblasting, comprising carbon powder having a new Mohs hardness of 2.5 to 7.0;

[0017] 2. The abrasive material for air blasting according to item 1, wherein the carbon powder is coke or anthracite;

[0018] 3. The abrasive material for air blasting according to 1 or 2, which is used for surface treatment of a separator for a fuel cell;

[0019] 4. A spacer for a fuel cell, wherein at least a portion of the surface is roughened using the abrasive material for air blasting of 3;

[0020] 5. The fuel cell separator according to 4, wherein at least a portion of the surface of a molded product of a composition comprising graphite powder; and an epoxy resin component comprising a main agent, a curing agent, and a curing accelerator is roughened using the above-mentioned abrasive material for air blasting;

[0021] 6. The fuel cell separator according to 4, wherein the arithmetic mean height Sa of the roughened surface is 0.5 to 1.5 μm;

[0022] 7. The fuel cell separator according to 4, wherein the number of polishing material residues with a particle size of 50 to 400 μm remaining on the roughened surface measured by direct / indirect measurement using VDA 19.2 is 500 or less;

[0023] 8. The fuel cell separator according to 4, wherein the contact resistance of the roughened surface is 7 mΩ·cm or less;

[0024] 9. A fuel cell separator, comprising a graphite powder; and a composition comprising an epoxy resin component including a main agent, a curing agent and a curing accelerator, wherein at least a portion of the surface of a molded product is roughened with an abrasive material, wherein:

[0025] The number of abrasive residues with a particle size of 50 to 400 μm remaining on the roughened surface measured by direct / indirect measurement using VDA 19.2 is 500 or less.

[0026] The arithmetic mean height Sa of the roughened surface is 0.5 to 1.5 μm.

[0027] Effects of the Invention

[0028] The abrasive for air blasting of the present invention contains carbon powder having a predetermined hardness and therefore has a property that it is difficult to remain on the surface of the blasting object during blasting.

[0029] The fuel cell separator subjected to the surface roughening treatment with the abrasive by air blasting has no abrasive residue on the surface and has excellent conductivity and adhesion with the gasket. DETAILED DESCRIPTION

[0030] Hereinafter, the present invention will be described in more detail.

[0031] [1] Abrasives for air blasting

[0032] The abrasive material for air blasting of the present invention is characterized by containing carbon powder having a new Mohs hardness of 2.5 to 7.0. The new Mohs hardness is an index of hardness defined by further subdividing the standard Mohs hardness index using 10 grades of hardness into 15 grades of hardness, and is also called modified Mohs hardness.

[0033] In the present invention, if the new Mohs hardness is outside the above range, residues are likely to form and remain on the surface of the blasting object, and when used as an abrasive material for air blasting of a spacer for a fuel cell, the reduction of the contact resistance of the roughened surface becomes insufficient, and the adhesion with the gasket becomes insufficient.

[0034] The new Mohs hardness is preferably in the range of 2.5 to 6.0, more preferably in the range of 2.5 to 5.5, and even more preferably in the range of 2.5 to 5.0.

[0035] The carbon powder is not particularly limited as long as it satisfies the above-mentioned new Mohs hardness. In the present invention, examples thereof include coal, charcoal, anthracite, glassy carbon, and coke. Among them, anthracite and coke are preferred, and coke is more preferred.

[0036] The average particle size (d=50) of the abrasive material for air blasting of the present invention is not particularly limited as long as it is within the range of general abrasive materials. If it is considered to be used as an abrasive material for surface treatment of separators for fuel cells, it is preferably 50 to 400 μm, more preferably 55 to 300 μm, further preferably 58 to 200 μm, and further preferably 60 to 190 μm.

[0037] [2] Fuel cell separators

[0038] The fuel cell separator according to the present invention is obtained by roughening the surface of at least a portion of a molded product of a fuel cell separator composition using the above-mentioned abrasive material for air blasting.

[0039] In the present invention, the fuel cell separator composition can be appropriately selected from conventional compositions used for producing fuel cell separators. For example, a composition containing graphite powder and an epoxy resin component containing a main agent, a curing agent, and a curing accelerator can be preferably used.

[0040] The graphite powder is not particularly limited, and either natural graphite or artificial graphite can be used.

[0041] The artificial graphite powder can be appropriately selected from artificial graphite powders conventionally used for fuel cell separators, and specific examples thereof include artificial graphite obtained by burning needle coke and artificial graphite obtained by burning lump coke.

[0042] On the other hand, the natural graphite powder can be appropriately selected from natural graphite powders conventionally used for separators for fuel cells, and specific examples thereof include bulk natural graphite and flaky natural graphite.

[0043] In addition, these graphite powders may be used alone or in combination of two or more.

[0044] The average particle size d50 of the graphite powder is not particularly limited, but is preferably 10 to 200 μm, more preferably 15 to 140 μm, and further preferably 20 to 80 μm in view of improving conductivity (reducing contact resistance).

[0045] In addition, the average particle diameter d50 in the present invention refers to the median diameter in the particle size distribution measurement using the laser diffraction method.

[0046] As the main agent constituting the epoxy resin component, as long as it has an epoxy group, there is no particular limitation, for example, o-cresol novolac type epoxy resin, phenol novolac type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, biphenyl type epoxy resin, biphenyl aralkyl type epoxy resin, trisphenol type epoxy resin, brominated epoxy resin, dicyclopentadiene type epoxy resin, biphenyl novolac type epoxy resin, etc. can be listed, these can be used individually or two or more kinds can be used in combination. Among these, preferred single o-cresol novolac type epoxy resin, single biphenyl type epoxy resin, and their mixtures.

[0047] The epoxy equivalent of the epoxy resin used in the present invention is not particularly limited, but is preferably 180 to 209 g / eq.

[0048] In addition, as a curing agent, a phenolic resin is preferred. As specific examples thereof, novolac type phenolic resin, cresol novolac type phenolic resin, resol type phenolic resin, aralkyl modified phenolic resin, biphenyl novolac type phenolic resin, trisphenol methane type phenolic resin, etc. can be listed, and these can be used alone or in combination of two or more. Among these, novolac type phenolic resin is preferred.

[0049] The hydroxyl equivalent of the phenolic resin used in the present invention is not particularly limited, but is preferably 95 to 140 g / eq, and more preferably 100 to 115 g / eq.

[0050] The curing accelerator is not particularly limited as long as it promotes the reaction between the epoxy group and the curing agent, and examples thereof include phosphine compounds, amine compounds, imidazole compounds, and the like. Among these, in the present invention, an imidazole compound having an aryl group at position 2 is preferably used. Specific examples of the aryl group include phenyl, tolyl, naphthyl, and the like, and phenyl is preferred. Specific examples of the imidazole compound having an aryl group at position 2 include 2-phenylimidazole, 2-phenyl-4-methylimidazole, and the like.

[0051] Furthermore, in addition to the above-mentioned components, the composition used in the present invention may also contain an optional component such as an internal mold release agent as appropriate.

[0052] As an internal mold release agent, it can be appropriately selected from various internal mold release agents conventionally used in the molding of spacers. Specific examples thereof include stearic acid wax, amide wax, montanic acid wax, carnauba wax, polyethylene wax, etc. These can be used individually or in combination of two or more.

[0053] In the composition used in the present invention, the amount of the epoxy resin component (main agent, curing agent and curing accelerator) is not particularly limited, but is preferably 10 to 50 parts by mass, more preferably 20 to 40 parts by mass, based on 100 parts by mass of the graphite powder.

[0054] In this case, the curing agent is preferably blended in an amount of 0.98 to 1.08 equivalents, more preferably 0.99 to 1.05 equivalents, relative to the main agent.

[0055] The amount of the curing accelerator used is not particularly limited, but is preferably 0.1 to 5 parts by mass, more preferably 0.5 to 2 parts by mass, based on 100 parts by mass of the mixture of the main agent and the curing agent.

[0056] Furthermore, when an internal mold release agent is used, the amount thereof used is not particularly limited, but is preferably 0.01 to 3.0 parts by mass, more preferably 0.05 to 1.5 parts by mass, based on 100 parts by mass of the graphite powder.

[0057] The composition used in the present invention can be prepared by mixing graphite powder, a main agent, a curing agent and a curing accelerator in an arbitrary order at a predetermined ratio. In this case, as a mixer, for example, a planetary mixer, a ribbon blender, a rediger mixer, a Henschel mixer, a rock mixer, a Nauta mixer, etc. can be used.

[0058] In addition, when using an internal mold release agent, the mixing order is also arbitrary.

[0059] The above composition is, for example, placed in a predetermined mold and compression molded to obtain a molded body (spacer precursor). As the mold used, a mold for making a fuel cell spacer that can form a groove that becomes a gas flow path on one or both sides of the surface of the molded body can be listed.

[0060] The conditions for compression molding are not particularly limited, but the mold temperature is 150 to 190° C. and the molding pressure is 30 to 60 MPa, preferably 30 to 50 MPa.

[0061] The compression molding time is not particularly limited and can be appropriately set within a range of about 3 seconds to 1 hour.

[0062] In addition, after compression molding, in order to promote thermal curing, it may be further heated at 150 to 200° C. for about 1 to 600 minutes.

[0063] In the present invention, the obtained molded body (fuel cell separator precursor) is subjected to a surface roughening treatment using the abrasive for air blasting of the present invention.

[0064] In this case, the above-mentioned abrasive materials for air blasting may be used individually to perform the surface roughening treatment, or two or more kinds of abrasive materials may be used in combination to perform the surface roughening treatment.

[0065] The blasting pressure during air blasting varies depending on the particle size of the abrasive and the like, and therefore cannot be unconditionally specified, but is preferably 0.1 to 1 MPa, and more preferably 0.15 to 0.5 MPa.

[0066] The conveying speed during the air blasting treatment cannot be determined in a general manner, but is preferably 0.1 to 5 m / min, more preferably 0.3 to 2 m / min, and still more preferably 0.5 to 1.5 m / min.

[0067] The surface roughening treatment may be applied to a part of the surface of the molded body or to the entire surface, preferably to the entire surface. In addition, the surface roughening treatment may be applied to one surface or to both surfaces.

[0068] When a part of the molded body is roughened, it is preferred that at least one surface, the surface of the seal portion with the gasket and the bottom and top of the groove serving as the gas flow path, be roughened.

[0069] The fuel cell separator of the present invention that has been subjected to the above-mentioned roughening treatment has the characteristic that the residue of the abrasive material remaining on the roughened surface is small, for example, it has the following characteristics: the residue of the abrasive material with a particle size of 50 to 400 μm remaining on the roughened surface measured by direct / indirect measurement using VDA19.2 is 500 or less, preferably 400 or less, and more preferably 300 or less. It should be noted that in the present invention, the above-mentioned number of particles is the total number of particles of 50 to 400 μm measured by extracting the attached abrasive material from any three locations on the roughened surface using a tape lift pad dedicated to the monitor using a surface cleanliness particle monitor measured directly / indirectly according to VDA19.2. For example, in a fuel cell separator having a gas flow path, a sealing portion and a cooling flow path, the polishing material attached to the surface is extracted from one location of each of the gas flow path, the sealing portion and the cooling flow path using a tape lifter pad and the number of particles of 50 to 400 μm is measured.

[0070] In the fuel cell separator of the present invention, the arithmetic mean height Sa of the roughened surface is preferably 0.5 to 1.5 μm, more preferably 0.6 to 1.5 μm, from the viewpoint of reducing contact resistance.

[0071] The contact resistance of the roughened surface is preferably 7.0 mΩ·cm or less, and more preferably 6.5 mΩ·cm or less. The lower the contact resistance, the better, and the lower limit thereof is usually about 3.0 mΩ·cm.

[0072] Furthermore, the fuel cell separator of the present invention subjected to the above-mentioned roughening treatment has a feature of excellent adhesion to the gasket because less residue of the polishing material remains on the roughened surface.

[0073] The gasket is usually formed on the peripheral portion (sealing portion) of the surface of the roughened molded body having the groove serving as the gas flow path.

[0074] In the present invention, the material for the gasket can be appropriately selected from materials that have been used as gasket materials for spacers in the past. Specific examples thereof include rubber materials such as natural rubber, silicone rubber, SIS copolymer, SBS copolymer, SEBS, ethylene-propylene rubber, ethylene-propylene-diene rubber, acrylonitrile-butadiene rubber, hydrogenated acrylonitrile-butadiene rubber, chloroprene rubber, acrylic rubber, fluorine-based rubber, butyl rubber, hydrogenated isobutylene rubber, and hydrogenated butadiene rubber.

[0075] As a method for forming a gasket, for example, there can be listed a method of bonding or fusing a gasket pre-formed in a sheet or plate shape to the above-mentioned peripheral portion (sealing portion) of the molded body; a method of applying a composition containing the above-mentioned rubber material on the surface of the above-mentioned peripheral portion of the molded body and then curing it to form a gasket, etc., and the latter method of applying and then curing it is preferred.

[0076] The coating method is not particularly limited, and examples thereof include drop casting, spin coating, blade coating, roll coating, rod coating, die coating, inkjet, printing (flexographic printing, gravure printing, lithography, screen printing, etc.), etc., among which printing is preferred, and screen printing is more preferred.

[0077] The curing method may be appropriately selected from conventionally known vulcanization methods such as heating and irradiation with radiation such as electron beams.

[0078] In the case of a spacer having grooves on both sides and both sides being gas flow paths, gaskets are formed on both sides. In the case of a spacer having a gas flow path on one side, if sealing is also required for the opposite side (cooling surface), a gasket may be formed around the cooling surface as required. When gaskets are formed on both sides, the gaskets may be formed sequentially on each single side or simultaneously on both sides.

[0079] A fuel cell including the fuel cell separator of the present invention having excellent adhesion with a gasket can maintain stable power generation efficiency over a long period of time.

[0080] Generally, in the case of a solid polymer fuel cell, a plurality of unit cells consisting of a pair of electrodes that clamp a solid polymer membrane and a pair of spacers that clamp these electrodes to form a gas supply and exhaust flow path are arranged in parallel, and the fuel cell spacer of the present invention can be used as part or all of these multiple spacers.

[0081] Example

[0082] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples. It should be noted that the physical properties in the Examples were measured by the following methods.

[0083] [1] Average particle size d50 of graphite powder and abrasives for air blasting

[0084] The median diameter was measured by a laser diffraction method using a particle size distribution analyzer (MT3000 manufactured by Nikkiso Co., Ltd.).

[0085] [2] Arithmetic mean height Sa

[0086] The arithmetic mean height Sa specified in ISO 25178-2:2012 was measured for each surface of the gas flow channel groove bottom (concave portion) and the peak (convex portion) of each spacer sample before the gasket was formed using a laser microscope (LEXT OLS5000 manufactured by Olympus Corporation).

[0087] [3] Contact resistance

[0088] (1) Carbon paper + spacer sample

[0089] Two of the spacer samples before the gasket formation were stacked, carbon paper (TGP-H060 manufactured by Toray Industries, Inc.) was placed above and below, and copper electrodes were placed above and below, and a surface pressure of 1 MPa was applied in the vertical direction to measure the voltage by a four-terminal method.

[0090] (2) Carbon paper

[0091] Copper electrodes were placed above and below the carbon paper, a surface pressure of 1 MPa was applied in the vertical direction, and the voltage was measured by a four-terminal method.

[0092] (3) Contact resistance calculation method

[0093] From the voltage values ​​obtained in (1) and (2) above, the voltage drop between the spacer sample and the carbon paper was obtained, and the contact resistance was calculated by the following formula.

[0094] [4] Number of grinding material residues (number of particles)

[0095] Using a surface cleanliness particle monitor (manufactured by inthecno, PartSens) for direct / indirect measurement in accordance with VDA19.2, the abrasives attached to the surface were extracted from the gas flow path, seal part, and cooling flow path of the spacer before the gasket was formed using a dedicated tape lift pad at an average of one point each, and the number of particles of 50 to 400 μm was measured. The values ​​in the table are the total amount of abrasive particles attached to the gas flow path, seal part, and cooling flow path.

[0096] [5] Peeling of gasket

[0097] With respect to the sealing material (gasket) bonded to the separator, air at 0.2 MPa was sprayed for 2 seconds, and the presence or absence of peeling was visually evaluated.

[0098] [Example 1]

[0099] Relative to 100 parts by mass of graphite powder (artificial graphite, average particle size d50: 23 μm, average height: 8 μm), an epoxy resin component consisting of 20.4 parts by mass of epoxy resin (o-cresol novolac type epoxy resin, epoxy equivalent 198 g / eq), 10.7 parts by mass of phenolic resin (novolac type phenolic resin, hydroxyl equivalent 103 g / eq), and 0.25 parts by mass of 2-phenylimidazole was put into a Henschel mixer and mixed at 800 rpm for 3 minutes to prepare a composition.

[0100] The obtained composition was put into a mold for producing a spacer for a fuel cell, and compression molded under the conditions of a mold temperature of 185°C, a molding pressure of 36.6 MPa, and a molding time of 9 seconds to obtain a 240 mm×240 mm×2 mm molded body having a gas flow path groove.

[0101] Next, the entire surface of the obtained molded body was roughened by air blasting using a coke abrasive (new Mohs hardness: 4.5, average particle size: d50 = 180 μm) at a spray pressure of 0.25 MPa and a conveying speed of 1.5 m / min to obtain a separator for a fuel cell.

[0102] Next, ethylene-propylene-diene rubber was applied to the peripheral portion (sealing portion) of the roughened surface by screen printing, and then heat-cured at 175° C. for 30 minutes to form a gasket, thereby obtaining a fuel cell separator with a gasket.

[0103] [Example 2]

[0104] A fuel cell separator with a gasket was obtained in the same manner as in Example 1 except that the coke ground material was changed to anthracite ground material (new Mohs hardness: 2.7, average particle size: d50=60 μm).

[0105] [Comparative Example 1]

[0106] A fuel cell separator with a gasket was obtained in the same manner as in Example 1 except that the coke abrasive was changed to a melamine resin abrasive (new Mohs hardness: 4.0, average particle size: d50=200 μm).

[0107] [Comparative Example 2]

[0108] A fuel cell separator with a gasket was obtained in the same manner as in Example 1 except that the coke abrasive was changed to an acrylic resin abrasive (new Mohs hardness: 3.5, average particle size: d50=150 μm).

[0109] [Comparative Example 3]

[0110] A fuel cell separator with a gasket was obtained in the same manner as in Example 1 except that the coke ground material was changed to a glass powder ground material (new Mohs hardness: 6.5, average particle size: d50=100 μm).

[0111] [Comparative Example 4]

[0112] A fuel cell separator with a gasket was obtained in the same manner as in Example 1 except that the coke abrasive was replaced with a dry ice abrasive (new Mohs hardness: 2.0, average particle size: d50=3000 μm).

[0113] [Comparative Example 5]

[0114] A fuel cell separator with a gasket was obtained in the same manner as in Example 1 except that the coke abrasive material was changed to a natural graphite abrasive material (new Mohs hardness: 1.5, average particle size: d50=50 μm).

[0115] [Comparative Example 6]

[0116] A fuel cell separator with a gasket was obtained in the same manner as in Example 1 except that the coke abrasive was changed to an alumina abrasive (new Mohs hardness: 12, average particle size: d50=60 μm).

[0117] [Comparative Example 7]

[0118] A fuel cell separator with a gasket was obtained in the same manner as in Example 1 except that the coke abrasive was changed to a zirconium oxide abrasive (new Mohs hardness: 7.5, average particle size: d50=60 μm).

[0119] [Comparative Example 8]

[0120] A fuel cell separator with a gasket was obtained in the same manner as in Example 1 except that the coke abrasive was changed to a silicon carbide abrasive (new Mohs hardness: 12, average particle size: d50=60 μm).

[0121] The arithmetic mean height Sa, contact resistance, and polishing material residue count of the fuel cell separators before gasket formation obtained in Examples 1 and 2 and Comparative Examples 1 to 8 were measured and evaluated, and the gasket peelability of the fuel cell separators with gaskets was evaluated. The results are shown in Table 1.

[0122] [Table 1]

[0123]

[0124] As shown in Table 1, it is found that: for the fuel cell separators of Examples 1 and 2 that were air blasted with carbon powder having a new Mohs hardness of 2.5 to 7.0, the number of abrasive residues with a particle size of 50 to 400 μm on the surface was less than 500, and the arithmetic mean height Sa was adjusted to 0.5 to 1.5 μm, so they had excellent contact resistance and no gasket peeling.

[0125] On the other hand, in the spacers obtained in Comparative Examples 1 to 3 and subjected to air blasting with melamine resin, acrylic resin or glass powder, charged abrasives adhered to the spacer surface, resulting in a large amount of residue remaining and poor gasket adhesion.

[0126] It was found that the spacers obtained in Comparative Examples 4 and 5 and subjected to air blasting with dry ice or natural graphite had little abrasive residue, but had low new Mohs hardness and small arithmetic mean height Sa, and the reduction in contact resistance was insufficient.

[0127] It was found that in the spacers obtained in Comparative Examples 6 to 8 and subjected to air blasting with alumina, zirconia or silicon carbide, the abrasive adhered to and sunk into the spacers, resulting in a large amount of residue remaining and poor adhesion of the gasket.

Claims

1. An abrasive material for air blasting, comprising carbon powder having a new Mohs hardness of 2.5 to 7.

0.

2. The abrasive material for air blasting according to claim 1, wherein: The carbon powder is coke or anthracite. 3 . The abrasive material for air blasting according to claim 1 , which is used for surface treatment of a separator for a fuel cell.

4. A spacer for a fuel cell, wherein: At least a part of the surface is roughened using the abrasive material for air blasting according to claim 3.

5. The fuel cell separator according to claim 4, wherein: At least a portion of the surface of a molded product of a composition containing graphite powder and an epoxy resin component containing a main agent, a curing agent, and a curing accelerator is roughened using the abrasive material for air blasting.

6. The fuel cell separator according to claim 4, wherein: The arithmetic mean height Sa of the roughened surface is 0.5 to 1.5 μm.

7. The fuel cell separator according to claim 4, wherein: The number of abrasive residues having a particle size of 50 to 400 μm remaining on the roughened surface measured by direct / indirect measurement using VDA 19.2 is 500 or less.

8. The fuel cell separator according to claim 4, wherein: The contact resistance of the roughened surface is 7 mΩ·cm or less.

9. A fuel cell separator, wherein at least a portion of the surface of a molded product of a composition comprising graphite powder and an epoxy resin component is roughened with an abrasive material, wherein the epoxy resin component comprises a main agent, a curing agent, and a curing accelerator, wherein: The number of abrasive residues having a particle size of 50 to 400 μm remaining on the roughened surface measured by direct or indirect measurement using VDA 19.2 is 500 or less. The arithmetic mean height Sa of the roughened surface is 0.5 to 1.5 μm.

Citation Information

Patent Citations

  • Fuel cell separator

    JP2005197222A

  • Separator for fuel cell, and its manufacturing method

    JP2005332775A